Therapeutic potential of combination medicinal mushrooms (NevG) in ischemic stroke: correlating motor function, cognitive recovery, and hippocampal integrity in MCAO rats - Athirah Azlan, Nur; Noor Tuah, Misya Afiqah; Nik Ramli, Nik Nasihah; Muhammad, Hussin; Eshak, Zolkapli; Peng, Liao; Bo, Chen; Kumari, Yatinesh; Jazuli, Imran; Che Mohd Nasir, Che Mohd Nasril; Ling Sing, Syntyche Seow; Poh Guat, Cheng; et al. (Frontiers in Pharmacology, 2026)
BackgroundIschemic stroke is a major neurological disorder that is characterized by cognitive decline and sensorimotor impairment. Despite the potential of therapeutic effects and anti-inflammatory properties of medicinal mushrooms, most current research focuses on single-species effects rather than combined formulations. This gap highlights the need to investigate the potential of a combination of medicinal mushrooms named NevG, containing Lignosus rhinocerus, Hericium erinaceus, and Ganoderma lucidum, focusing on their therapeutic effects in the context of ischemic stroke.MethodsForty adult male Sprague–Dawley rats were randomly assigned to five groups (n = 8): normal, MCAO-induced, and NevG in oral doses of 250 mg/kg, 500 mg/kg, and 1,000 mg/kg for 28 days. Ischemia was induced using the Koizumi method and confirmed through triphenyltetrazolium chloride (TTC) staining and mNSS scoring. Cognitive abilities were assessed using the Morris water maze and T-maze tests, and sensorimotor function was evaluated using the open-field, rotarod, and pole tests. Mechanistic analyses involved measuring anti-inflammatory serum cytokine pathways (TNF-α, IL-1β, IL-6, and NF-κβ).ResultsNevG significantly reduced infarct volume by 32%–58% compared with the middle cerebral artery occlusion (MCAO) group (p < 0.05). Cognitive performance improved, with a 25%–46% reduction in the Morris water maze (MWM) escape latency (p < 0.01) and an increase in T-maze spontaneous alternation. Sensorimotor functions were enhanced, as evidenced by increases in the open-field test (OFT), rotarod retention time (p < 0.01), and decreased descent time in the pole test. The cresyl violet staining of the neurons in the hippocampus shows improvement in pyramidal cell counts, and the ultrastructural transmission electron microscope (TEM) analysis shows better preservation of the nucleus and mitochondria, intact myelin sheath, and improved axonal integrity. NevG significantly lowered the inflammatory serum cytokine level (p < 0.05) and promoted neuronal survival.ConclusionNevG demonstrates significant neuroprotective effects in ischemic stroke, achieved through reduced neuroinflammation and improved neuronal survival, indicating its potential as a natural therapeutic agent.